(Hetero)sexist microaggressions in practice. (21st July 2022) - Lobban, Rosemary; Luyt, Russell; McDermott, Daragh T
Abstract : Verbal microaggressions perpetuate inequalities and negatively impact wellbeing. Yet, there is little work on microaggressions in situ. We address this gap, connecting microaggressions research with scholarship concerning prejudice and discrimination in situated interaction, and focusing on (hetero)sexist microaggressions. Conversation analysis (CA) and membership categorisation analysis (MCA) are applied to excerpts of naturally-occurring and focus group conversation to determine what (hetero)sexist microaggressions look like in practice; how they affect conversations; and whether they map onto well-documented CA/MCA phenomena. Findings suggest that when people produce microaggressive utterances, they use various devices (e.g. pre-sequences, idioms, humour) to mitigate accountability. Furthermore, concerning recipients' reactions, the treatment of an utterance as microaggressive can involve hallmarks of dispreferred turns including hesitation and/or indirect challenges involving deletion/repair initiation. We therefore propose that such features are criteria for an utterance/sequence to be considered microaggressive. Moreover, such strategies suggest that speakers/recipients are agentic in the (re)production of (hetero)sexism, and therefore may be agentic in effecting change.   OPEN ACCESS CC BY-NC-ND: INV PAID